Analysis of angular dependence of strong-field tunneling ionization for CO2 - Zhao, Song-Feng; Jin, Cheng; Le, Anh-Thu; Jiang, T. F.; Lin, C. D. (My University, 2009)
We analyzed the discrepancy of the angular dependence of strong-field ionization for CO2 among the different theoretical calculations and experiments. Using a more accurate ground-state wave function of CO2 in the asymptotic region, we showed that the accuracy in the earlier tunneling ionization theory of Tong et al. [Phys. Rev. A 66, 033402 (2002)] is much improved. We also concluded that the angular dependence deduced from the experiment of Pavičić et al. [Phys. Rev. Lett. 98, 243001 (2007)] appears to be too narrowly distributed.